Engineered biochar supported layered double hydroxide-cellulose nanocrystals composite-: Synthesis, characterization and azo dye removal performance. (November 2022) - Zubair, Mukarram; Aziz, Hamidi Abdul; Ihsanullah, Ihsanullah; Ahmad, Mohd Azmier; Al-Harthi, Mamdouh A.
Abstract: In this work, engineered biochar decorated layered double hydroxides and cellulose nanocrystals (B–CuFe–CNC) biocomposites were synthesized by the facile ultrasonicated-co-precipitation technique. The biocomposite was investigated for purification of Eriochrome Black T (EBT) dye from water. The characterization results showed that the presence of CNC in biochar-layered double hydroxides resulted in a two-dimensional rod-like structure with excellent crystallinity, improved surface functionalities, and provides an attractive platform for the enhanced adsorption of azo anionic dye molecules. The adsorption system was appropriately demonstrated by the BBD-RSM (R 2  > 0.994). The biocomposite exhibited higher EBT adsorption in the acidic pH range (2–5) due to strong electrostatic and chemical interactions. The kinetic and isotherm results were well demonstrated by pseudo-second order, Freundlich, and Redlich Peterson models. The maximum adsorption capacity of biocomposite was 876.2 mg/g achieved within 45 min. The spectroscopic analyses imply that the high removal of EBT by biocomposite is mainly governed by electrostatic attraction, hydrogen bonding, and chemical/metal complexation mechanisms. The biocomposite maintained high EBT removal after six successive adsorption cycles and excellent dye adsorption in the different water matrices. The results suggest that tailoring biochar properties with layered double hydroxide and CNC is a promising way for the enhanced removal of dye contaminants from wastewater. Graphical abstract: Image 1 Highlights: Biochar-CuFe-CNC biocomposites were fabricated by simple co-precipitation method. The biocomposite exhibited superior adsorption of Eriochrome Black T(EBT) dye. The adsorption capacity of B-CuFe-CNC was five and three folds higher than biochar and CuFe LDH. The presence of CNC improved the surface functionality and hydrophilicity.